Friendlier than a Banquet: A Tasty Literary Miniature by Libanius (LIB., Ep. 996F) (Minerva, 2017)
Libanius’ epistle 996 seems to have gone unnoticed in the history of classical and philological studies, despite its representativeness in form and content, as well as its relevance for the study of Rhetoric and Communication Theory, among other disciplines. In a few lines, Libanius draws an intricate network of allusions concerning the Hellenic notion of banquet. He brings together very different literary genres from canonical authors, while, at the same time, it fulfils an aesthetic and psychological purpose, within the framework of a carefully strategic structure of rhetorical figures. Among other considerations, the rhetor suggests the importance of knowledge and education, identified with the rhetoric and represented by the notion of banquet, which must be linked to justice and virtue, in order to become genuine wisdom. A variety of linguistic uses of this epistle, but especially that of the banquet, illustrate a conscious semantic distinction (shown by the specific context of the epistle) between the literary and the literal. This involves interdisciplinary implications such as the philosophical dichotomy between being and existing.
Keywords: Libanius; hellenism; late antiquity; epistolography; rhetoric; banquet; friendship